Effectiveness of Health Education Diabetic Foot Care with Leaflet and Audiovisual Media Toward Knowledge - Yusuf Efendi (Journal for Quality in Public Health, 2019)
Diabetic foot care is a foot treatment performed on diabetics to prevent ulcers (sores). The steps that must be done are, check the blood sugar levels regularly, wash your feet with warm water, check for injuries to the feet, do nail care and use footwear. Audio visual media is one of the media of counseling that attracts and stimulates more senses than media leaflets. This study aims to determine the effectiveness of audio visual media and leaflets on improving knowledge of foot care knowledge in people with diabetes mellitus. This research is a type of Pre Experimental research with the design of one group pretest and postest. The study was conducted by dividing respondents into 2 groups classified as 1) groups given health education through media leaflets and 2) groups given health education through Audiovisual media. The population of this study amounted to 106 people with a sample of 102 people, each of 52 samples in each health center determined by purposive sampling based on inclusion and exclusion criteria. The analysis used is the Wilcoxon Sign Range Test and Mann-Whitney test analysis. The results showed that Leaflet and Audiovisual media were able to provide an increase in changes in the level of knowledge (p = 0.032 and 0.017) after counseling. So this study proves the use of audio visual media is more effective for health education activities in improving knowledge of Deabetic foot care.